Improvement proposals for Lean Six Sigma projects applied in the automotive sector (International Journal of Geoscience, Engineering and Technology, 2022)
This work aims to evaluate the application of the Lean Six Sigma (LSS) approach in two projects carried out in the automotive sector, demonstrate the benefits of using the method in the field, and criticize the application of improvement projects, to point out changes, points to be modified and/or added to improve results. Thanks to the Web of Science, several scientific articles that published LSS projects were examined, being filtered with some criteria, such as the year of publication and the application of the methodology. The first selected aims to identify problems in the production line, validate opportunities and implement improvements, and the second aims to analyze the impact of implementing the LSS in reducing waste in internal logistics. For this, studies were carried out in the areas of project management, production planning and control, logistics, and quality engineering. In the unfolding of this work, the steps resulting from the application of the LSS are presented and analyzed and proposals for improvements are carried out, accompanied by the creation of graphs and tools that fit into each phase of the DMAIC (Define, Measure, Analyze, Implement and Control).